Management Audit to Assess the Effectiveness of Human Resource Function at CV. Aneka Grafika Jatimulyo Malang City - Abuk, Marselina; Nur Ida Iriani; Warter Agustim (International Research and Development for Human Beings (IRDH), 2025)
The purpose of this study is to determine audit management in assessing the effectiveness of the function of human resources in CV. Aneka Grafika Malang City. Types of Qualitative Descriptive Research. The informant used by one person, namely the factory manager CV. Aneka Grafika Malang City. The instrument uses interview guidelines. Analysis uses descriptive analysis that focuses on employee recruitment, special training, compensation and service, occupational health and safety, and termination of employment. The results showed that the employee recruitment process at CV. Aneka Graphic Jatimulyo Malang City is carried out flexibly based on operational needs by emphasizing specific qualifications and direct practice -based training. Training uses the on-the-job training method with senior employee assistance to accelerate adaptation and improve skills. Structured compensation systems, such as incentives and performance bonuses, motivate discipline and appreciation for employee contributions. The implementation of work health and safety goes well through the Safety Signs and BPJS guarantees, creating a safe work environment. Termination of employment is carried out ethically by gradual coaching to provide opportunities for improvement of employee performance. Manager CV. Aneka Graphic City of Malang is advised to increase the transparency of recruitment, involve technology, and add soft skills in training. Evaluation of the compensation system needs to be done regularly by adding performance -based awards. Occupational health and safety programs must be strengthened through training, simulations, and adequate medical facilities. Directed performance evaluation and career development can be an alternative before termination of employment, supported by a clear agreement with outsourcing.